Dengue Serosurvey in Sint Eustatius - Leslie, Teresa (Public Library of Science, 2014)
Four distinct serotypes of dengue viruses (DENV) are the cause of re-emerging dengue fever (DF) and dengue hemorrhagic fever (DHF). Dengue circulation in the Caribbean has gone from none or single serotype to multiple serotypes co-circulating with reports of continuing cycles of progressively more severe disease in the region. Few studies have investigated dengue on Sint Eustatius. Blood samples were collected to determine the prevalence of antibodies against dengue in the Sint Eustatius population. Greater than 90% of the serum samples (184 of 204) were positive for anti-flavivirus antibodies by enzyme linked immunosorbance assay (ELISA). Plaque reduction neutralization test (PRNT), specific for dengue viruses, showed that 171 of these 184 flavivirus antibody positive sera had a neutralization titer against one or more DENV serotypes. A majority of the sera (62%) had neutralizing antibody to all four dengue serotypes. Only 26 PRNT positive sera (15%) had monotypic dengue virus neutralizing antibody, most of which (20 of 26) were against DENV2. Evidence of infection with all four serotypes was observed across all age groups except in the youngest age group (10–19 years) which contained only DENV2 positive individuals. In a multiple logistic regression model, only the length of residence on the island was a predictor of a positive dengue PRNT(50) result. To our knowledge this is the first dengue serosurveillance study conducted on Sint Eustatius since the 1970s. The lack of antibodies to the DEN1, 3, and 4 in the samples collected from participants under 20 years of age suggests that only DEN2 has circulated on island since the early 1990s. The high prevalence of antibodies against dengue (83.8%) and the observation that the length of time on the island was the strongest predictor of infection suggests dengue is endemic on Sint Eustatius and a public health concern that warrants further investigation.